Interatomic coulombic decay in (HF)n,(n=2-3) clusters using CAP/EOM-CCSD method - Ghosh, Aryya; Pal, Sourav; Vaval, Nayana (Molecular Physics, 2013)
The equation-of-motion coupled-cluster method along with the complex absorbing potential has been applied to study the interatomic Coulombic decay mechanism in hydrogen-bonded clusters. We have applied this method to calculate the lifetime of the F 2s inner-valence ionised state of (HF)(n) (n = 2-3) clusters. The lifetime is found to be very short and decreases substantially with increasing the number of HF monomer.
Keywords: complex absorbing potential (CAP); equation-of-motion coupled-cluster (EOM-CC); HF clusters; interatomic Coulombic decay (ICD)